Real Urban Traffic Flow Chaotic Phase Space Study - Zhang, L.D.; Wang, Y. L.; Sun, Zh. Q.; Pan, J.Sh (2008 11th International IEEE Conference on Intelligent Transportation Systems, 2008)
Phase space reconstruction is the base of chaotic traffic flow prediction. To determine objectively the embedding delay time tau and embedding dimension m of real urban traffic flow time series chaotic phase space, we put forward a new kind of average calculation method. For delay time value, we first calculated its value of single day with auto-correlation and improved auto-correlation function, then we averaged seven days' values to degrade error. As to embedding dimension, we studied it with G-P algorithm and CAO algorithm respectively on base of data processing. Last, the method's feasibility was tested by analyzing the chaotic characteristics of Ji'nan city traffic flow and the reference parameters were offered, i.e.tau =14 and m=4.